(untitled) (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2024)
Background: Discovered over 200 million children below five years is not developing according to age. Bantul district in the year 2008 there is still early detection of growth that have not reached 100%, based on data from at the PHC Imogiri I 78,88%, PHC Imogiri II82,06%. While the number of babies who are given exclusive breast feeding at the PHC Imogiri I 45,75% and PHC Imogiri II19,59%. In the area of PHC Imogiri I, found delays in the development of age-appropriate or not is in the village of Wukirsari 6 of 284 infants, in the village of Girirejo 2 of 50 infants, in the village of Karangtalun 3 of 7 infants, and in the village of Imogiri 1 of 42 such infants and there 5 infants who experience age-appropriate development was not on fine motor development. Objective: To determine the correlation grant of age complementary feeding with interference trend growth fine motor in the area of work Public Health Center Imogiri I, Bantul, Yogyakarta. Method: The study was an analytical survey with cross sectional approach. The subjects were 0-12 month-old baby at the PHC Imogiri I sample as many as 413 infants with 133 infants using a quota sampling technique. This is a checklist of research instruments and sheet DDST II. Analysis of data using multivariate statistical test that is chi square with significancy 0,05 level. Results: The proportion of infants who were given complementary feeding before the age of 6 months was 26,3%, infants who experienced fine motor development according to age as much as 73,3%. The magnitude of risk infants experiencing fine motor developmental delay infants who were given complementary feeding before the age of 6 months was 31,4% and the risk of infants experiencing fine motor developmental delay infants given complementary feeding 6 months starting from the age of 6,1%. Conclusion: The administration of the complementary feeding before the age of 6 months are risk factors of the occurrence of fine motor development disorders in infants. Keywords: Giving Complementary Feeding, Fine Motor Development